2019
DOI: 10.33753/mandiri.v3i2.86
|View full text |Cite
|
Sign up to set email alerts
|

Faktor-faktor Determinan Kemandirian Wanita dalam Berwirausaha untuk Wilayah Banten

Abstract: AbstrakPenelitian ini berupaya untuk mengukur kemandirian wirausahawan wanita dengan melihat kepada faktorfaktor yang mempengaruhinya, antara lain berupa: akses terhadap teknologi, pengalaman pernah kerja, kepemilikan anak, jumlah modal awal, dan tingkat pendidikan yang tinggi. Sampel yang diambil sebanyak 193 wirausahawan wanita yang memiliki usaha di wilayah provinsi Banten, dimana peneliti memberikan quesioner yang dijawab oleh responden. Metode untuk analisis data yang digunakan ialah model regresi binary … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…The results of this study which indicate a positive and significant influence of the independence factor on the success of woman entrepreneurs are supported by research (Saputri et al, n.d.) which revealed that independence and family support factors had a positive and significant influence on woman entrepreneurs. On research (Surahman et al, 2019) also explained that the determinants of independence have a significant influence on woman entrepreneurs.…”
Section: Structural Modelmentioning
confidence: 98%
“…The results of this study which indicate a positive and significant influence of the independence factor on the success of woman entrepreneurs are supported by research (Saputri et al, n.d.) which revealed that independence and family support factors had a positive and significant influence on woman entrepreneurs. On research (Surahman et al, 2019) also explained that the determinants of independence have a significant influence on woman entrepreneurs.…”
Section: Structural Modelmentioning
confidence: 98%